The Effect of Islamic Financial Literacy, Religious Commitment, and Brand Image on the Saving Interest of Residents of Bandung Among Bank Muamalat Indonesia Customers - Ricky Dwi Patria; Muwwahid Billah; Saepul Rahmat (Winter Journal: IMWI Student Research Journal, 2026)
Islamic banking has experienced significant development in Indonesia; however, its market share remains relatively low compared with conventional banking, despite Indonesia having the largest Muslim population in the world. This condition indicates that public interest in using Islamic banking services, particularly saving products, is still influenced by several factors, including Islamic financial literacy, religious commitment, and brand image. This study aimed to examine the effects of Islamic financial literacy, religious commitment, and brand image on the saving interest of residents of Bandung City who are Bank Muamalat Indonesia customers. This research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 100 respondents selected using a purposive sampling technique. The data were analyzed using descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis. The results showed that Islamic financial literacy, religious commitment, and brand image had positive and significant effects on saving interest. Among these variables, brand image had the strongest influence, followed by Islamic financial literacy and religious commitment. Simultaneously, the three independent variables explained 70.5% of the variation in saving interest. The study concluded that improving Islamic financial literacy, strengthening religious values in financial decision-making, and enhancing a trustworthy brand image are essential strategies for increasing public interest in saving at Bank Muamalat Indonesia.